2018
DOI: 10.3390/su10041236
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Patterns of Extreme Temperature across the Huai River Basin, China, during 1961–2014, and Regional Responses to Global Changes

Abstract: Global warming and its relevant effects have aroused increasing human concerns in recent decades. These anomalies are likely influencing vegetation dynamics and ecosystem stability. This paper aims to dissect extreme temperature variations in both space and time, and related regional responses to global warming in the Huai River Basin. Using the daily maximum and minimum air temperature at 153 stations across the Huai River Basin, China, covering the period of 1961-2014, trends and relations amongst extreme ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…Ma et al [18] discussed and studied the detailed characteristics of the future changes in summer heat waves over three major urban agglomerations (Beijing-Tianjin-Hebei (BTH) region; the Yangtze River Delta (YRD); the Pearl River Delta (PRD)) in Eastern China under the 1.5 and 2.0 • C warming scenarios, and they found that the predicted change in the heat wave index in urban areas is much higher than that in non-urban areas, which means that urban areas will face higher heat-related disease or environmental risks than suburban or rural areas in the future. In addition, studies on the spatiotemporal characteristics of extreme heat events in the Yellow River Basin [19], the Huaihai Basin [20], the Qinghai-Tibet Plateau [21], and other regions showed that the change in extreme temperature will lead to regional climate change and be affected by many factors.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al [18] discussed and studied the detailed characteristics of the future changes in summer heat waves over three major urban agglomerations (Beijing-Tianjin-Hebei (BTH) region; the Yangtze River Delta (YRD); the Pearl River Delta (PRD)) in Eastern China under the 1.5 and 2.0 • C warming scenarios, and they found that the predicted change in the heat wave index in urban areas is much higher than that in non-urban areas, which means that urban areas will face higher heat-related disease or environmental risks than suburban or rural areas in the future. In addition, studies on the spatiotemporal characteristics of extreme heat events in the Yellow River Basin [19], the Huaihai Basin [20], the Qinghai-Tibet Plateau [21], and other regions showed that the change in extreme temperature will lead to regional climate change and be affected by many factors.…”
Section: Introductionmentioning
confidence: 99%
“…The study area of arable land and agricultural population in HRB accounted for 10% and 20.4% respectively, and providing 20% of China's agricultural products [24,25]. Therefore, irrigated agricultural production is vital to China's food security [26][27][28][29]. However, uneven distribution of precipitation in time and space in the HRB leads to frequent droughts and floods.…”
Section: Introductionmentioning
confidence: 99%